2003
DOI: 10.1124/mol.64.5.1126
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of α1B-Adrenergic Receptors with Defects in G Protein Coupling: Ligand-Induced Protection from Receptor Instability

Abstract: The biochemical basis for the unexpected agonist-induced upregulation of the number of radioligand binding sites for two mutated ␣ 1B -adrenergic receptors reported previously was investigated. Up-regulation was independent of the expression vector used and was not prevented by cycloheximide or actinomycin D, eliminating several potential transcriptional mechanisms and new receptor protein synthesis. Antagonists were also able to induce up-regulation, suggesting that ligand occupancy without signal generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Whether the same mechanism of action underlies all of these four increases in the α 1D ‐AR populations is uncertain. A new concept is that GPCRs may have inherent instability and therefore become downregulated, and that antagonists may stabilize receptor conformations that are less prone to downregulation (Prinster et al ., 2003; Zeng et al ., 2003). Thus, not only blocking of constitutively active receptors but also stabilization of unstable receptors, could explain the previously observed antagonist‐mediated increment in membrane‐localized α 1D ‐adrenoceptors (McCune et al ., 2000; see Garcia‐Sainz & Villalobos‐Molina, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the same mechanism of action underlies all of these four increases in the α 1D ‐AR populations is uncertain. A new concept is that GPCRs may have inherent instability and therefore become downregulated, and that antagonists may stabilize receptor conformations that are less prone to downregulation (Prinster et al ., 2003; Zeng et al ., 2003). Thus, not only blocking of constitutively active receptors but also stabilization of unstable receptors, could explain the previously observed antagonist‐mediated increment in membrane‐localized α 1D ‐adrenoceptors (McCune et al ., 2000; see Garcia‐Sainz & Villalobos‐Molina, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that phosphorylation by GRK is only a requirement for internalization. In contrast, mutations in the PKC phosphorylation sites in the C tail gave rise to "PKC-site mutants", which demonstrated partial impairment in sequestration and endocytosis but completely diminished down-regulation, indicating an important role for PKC in this process (Prinster, 2003).…”
Section: α 1 -Adrenoceptorsmentioning
confidence: 97%